Perawatan maloklusi Klas III pada usia tumbuh kembang - Nada Ismah (DiscoverSys Inc., 2010)
Various controversies arise on the appropriate treatment time to treat class IIImalocclusion at the development age. One reason for delay is that the treatment willmake the treatment period longer. Nevertheless, there are other reasons that believethe class III malocclusion must be treated as soon as possible. Accuracy ofexamination is required to obtain the proper diagnosis to determine treatmentoptions. Clinical conditions found in the class III malocclusion can be underdevelopedof maxillae, overdeveloped the mandible, or combination of both. Treatment of classIII malocclusion at the growing age may prevent further severity. A case report of 11yearold boy with class III malocclusion. He is treated with fixed orthodontics toremove obstruction on the maxillae growth. Many treated progression are obtained,although it is still continuing to be continued to maintain the treatmentstabilization. Initial treatment for the class III Malocclusion at the growing age canprevent further severity.